Carbon Dioxide Injection and Asphaltene Precipitation in Light Oil Reservoirs - Alta'ee, Ali F. (2010)
Gas injection is one of the oldest methods for enhanced oil recovery (EOR). Hydrocarbon and non-hydrocarbon gases have been used as injection fluids. CO2 injection is one of the successful and most commonly used technique for EOR. Injection of CO2 in light oil (>30˚ API) reservoirs may cause asphaltene precipitation resulting serious production and reservoir problems such as porosity alteration, permeability reduction, plugging of wellbore and blocking of production system. In most cases of CO2 injection in light oil reservoirs the probability of asphaltene precipitation is either ignored or not expected for two reasons. Firstly, the asphaltene content in most light-oil reservoirs is very small (0.1 wt %). Secondly, the reservoir had no previous asphaltene precipitation problem during its primary production process. Mechanism of asphaltene precipitation is not fully known. Nevertheless, it is generally understood that changes in composition of reservoir fluids, pressure, and temperature would lead to asphaltene precipitation. This paper presents a review of important factors that lead to asphaltene precipitation during CO2 injection in light oil reservoirs such as fluid composition changes due to CO2 injection, effect of CO2 concentration, and effect of first and multiple contact of CO2. The nature and structure of asphaltene and the colloidal properties are discussed including reported previous laboratory studies and field applications from published technical papers and field reports. Recommendations for asphaltene precipitation studies have been presented